What roles should the government play in fostering the advancement of the internet of things?. (June 2019) - Lee, Gwanhoo
Abstract: The Internet of Things (IoT) has the potential to transform the way we live, work, do business, and meet the needs of the public. While IoT's potential benefits for economic growth and social welfare appear to be indisputable, IoT faces several technological, social, legal, and regulatory policy challenges, ranging from interoperability and spectrum availability to cybersecurity and privacy. These challenges can and should be addressed by the joint efforts of a wide range of stakeholders from the public and private sector. The advancement of IoT depends in part on how policymakers respond to the opportunities and challenges associated with it. This research aims to identify the potential roles for the government in fostering the advancement of IoT innovation and adoption. To this end, we analyze data collected from 177 documents of public comments submitted to the U.S. National Telecommunications and Information Administration and from a focus group discussion with senior managers. Our content data analysis results in a set of recommendations for the government in terms of general policy principles, specific policy prescriptions, and governance and process approach that facilitate policy development. Highlights: This research addresses this question: "What roles should the government play in fostering the advancement of IoT?". This research analyzes 177 documents of public comments in response to the NTIA's request for comments. Our findings are grouped into general policy principles, specific policies, and governance and process approach. The general policy principles advocate a consistent, light-touch, evidence-based regulatory approach. We recommend seven prescriptions for specific policies and three prescriptions for governance and process.